Hyperglycemic stress induces oxidative damage of enteric glial cells by triggering redoxosomes/p66SHC activation - Yanmin Jiang; Lan Xu; Xue Zhu; Xiaowei Zhu; Xiang Xu; Jianbo Li (Taylor & Francis Group, 2024)
ABSTRACTObjectives Diabetic gastrointestinal dysfunction (DGD) is a serious complication of diabetic mellitus (DM), affecting the enteric nervous system (ENS), particular enteric glial cells (EGCs). This study aimed to elucidate the effects and underlying molecular mechanisms of hyperglycemic stress on EGCs in in vitro and in vivo models of DM.Methods In in vitro studies, enteric glial cell line CRL-2690 was exposed to hyperglycemia stress, and cell viability, cell apoptosis and oxidative damage were assessed. In in vivo studies, STZ-induced diabetic mice were constructed, and cell apoptosis and oxidative damage of EGCs in the duodenum of DM mice were assessed.Results The results showed that hyperglycemic stress markedly induced oxidative damage of EGCs in in vitro and in vivo models of DM. This damage was found to be dependent on the activation of redoxosomes, which involved the phosphorylation of SRC and Vav2, the up-regulation of active RAC1-GTP, and the activation of NADPH oxidase (NOX). Moreover, inhibitors of redoxosomes, such as the RAC1 inhibitor NSC23766 and the NOX inhibitor VAS2870, effectively mitigated the hyperglycemic stress-induced oxidative damage of EGCs. Additionally, inhibition of p66SHC, a downstream target of redoxosomes, attenuated oxidative damage of EGCs under hyperglycemic stress.Discussion Our findings suggest that the redoxosomes/p66SHC signaling is involved in the oxidative damage of EGCs during the pathological process of DGD. This signaling cascade may represent a potential therapeutic target for the treatment of DGD.